Los derechos de conciliación de la vida personal, familiar y profesional en las fuerzas armadas - Arias Domínguez, Ángel (2019)
The armed forces have a specific regulation of personal different from that applicableto other civil servants. This distinction derives mainly from the nature of the missionsthat are assigned the armed forces, which requires a particular organization and meansto carry out with the necessary effectiveness (discipline, rank, unit, specific values,etc.). The military, in fact, must have a specific regime for a better fulfill of its mission.But the specific arrangements should not serve as an obstacle to reconcile themilitary regime with the rest of the civil service. In other words: the military shouldonly be deprived of the rights granted to other public officials when such action isnecessary for the performance of their duties. The Spanish legislator recognizes theserights to the military and, precisely because of its singularity, has established protectivemeasures exclusively to them.